الضمانات غير المسماة في تنفيذ الإلتزامات التعاقدية - هناء بونعامة; رندة يونسي (My University, 2019)
Summary: The expansion and increasing importance of credit in modern times has led to a strong demand for guarantees. The fact that individuals and even banks and financial institutions grant credit to the production, distribution and consumption sectors inevitably increases the need for guarantees. The legislator's recognition of the creditor's privileged positions, whether legal, such as direct litigation, the right to detention and clearing or contractual, such as undersupply and loan insurance, so-called "unnamed guarantees" derived from traditional mechanisms that demonstrated that credit protection was less costly and less complex, which could cover the deficit of in-kind and personal insurance even if it had long been regarded as the most effective safeguards. However, the need to protect credit required the continued search for collateral, leading to the emergence of other guarantees introduced For example, property employment in the area of assurance has proven to have achieved significant effectiveness in addition to low and simple costs, The style of discourse has also brought about the safety that traders aspire to in their trustworthy relationships. Unnamed safeguards have proven their capacity and effectiveness in strengthening credit, but even under the comparative legislation they have regulated they are still confusing and ambiguous in determining their legal nature, owing to the evolution resulting from their flexibility. ............................ ملخص : أدى اتساع نطاق الائتمان وتزايد أهميته في العصر الحديث إلى الإقبال الشديد على فكرة الضمانات فقيام الأفراد وحتى البنوك والمؤسسات المالية بمنح الائتمان لقطاعات الإنتاج والتوزيع والاستهلاك يؤدي حتما إلى زيادة الحاجة إلى الضمانات وهذه الأخيرة قد تنوعت بسبب السباق المستمر نحو حماية الائتمان. ان اعتراف المشرع للدائن بمراكز متميزة سواء كانت قانونية كالدعوى المباشرة وحق الحبس والمقاصة، أو عقدية كالإنابة الناقصة وتأمين القرض، وهي ما اطلق عليها بالضمانات غير المسماة المستمدة من آليات تقليدية أثبت أن حماية الائتمان كانت بأقل كلفة وأقل تعقيدا وهو الأمر الذي يمكن من خلاله تغطية العجز الذي اكتنف التأمينات العينية والشخصية حتى و إن كانت قد إعتبرت ولمدة طويلة على أنها الضمانات الأكثر فعالية إلا أن ضرورة حماية الائتمان اقتضت الاستمرار في البحث عن ضمانات مما أدى إلى ظهور ضمانات أخرى مستحدثة، مثلا الملكية أثبت توظيفها في مجال الضمان أنها حققت فعالية لا يستهان بها بالإضافة إلى قلة وبساطة التكاليف، كما أن أسلوب الخطاب حقق هو الآخر الأمان الذي يطمح له التجار في علاقاتهم التي تقوم على الثقة. فالضمانات غير المسماة أثبتت وعن جدارة قدرتها وفعاليتها في تدعيم الائتمان، إلا أنها لا تزال وحتى في ظل التشريعات المقارنة التي قامت بتنظيمها تثير اللبس والغموض في مجال تحديد طبيعتها القانونية وذلك بسبب التطور الناجم عن مرونتها. ...................... Résumé L'expansion du crédit et son importance croissante à l'ère moderne ont entraîné une forte demande de garanties. Les particuliers, voire les banques et les établissements financiers, octroyant des crédits aux secteurs de la production, de la distribution et de la consommation augmentent inévitablement le besoin de garanties. La reconnaissance du créancier par le législateur, qu'elle soit légale, telle que la créance directe et le droit d'emprisonnement et de compensation, ou encore qu'un contrat, tel que la cession incomplète et la garantie du prêt, appelées garanties non garanties issues des mécanismes traditionnels, prouve que la protection du crédit était moins coûteuse et moins compliquée, Ce qui avait longtemps été considéré comme la garantie la plus efficace, mais la nécessité de protéger le crédit nécessitait la poursuite de la recherche de garanties, ce qui a conduit à l’émergence de nouvelles garanties nouvelles. L'efficacité d'un ajout important à l'absence de coût et de simplicité, et le style de la parole a obtenu est l'autre sécurité qui l'aspire aux commerçants dans leurs relations basées sur la confiance. Les garanties non classifiées ont prouvé leur valeur et leur efficacité dans la consolidation du crédit, mais même dans le cadre de la législation comparée qu’elles ont organisée, elles sont confuses et ambiguës dans la détermination de leur nature juridique en raison du développement de leur flexibilité.